RESEARCH OF VOLTAGE DEVIATION IN RURAL ELECTRICAL GRID WITH DISTRIBUTED GENERATION - Keshuov, S.A.; Shokolakova, Sh.; Saukhimov, A.A.; Shuvalovа E. (Scientific Journal of Pedagogy and Economics, 2018)
In accordance with the strategy for the development of energy in Kazakhstan in agriculture, it is necessary to solve the important problem of reducing the energy intensity of agricultural production [1, 2]. The key difficulties in integrating high-capacity generation of renewable energy sources(RES) into the grid are the planning and management of the system. Scenarios for studying the impact on the system depend on high or low load, high proportion or absence of wind/solar energy. For each case, the bus voltage is calculated and checked for compliance with permissible limits, the calculation of the flow distribution of active and reactive power, as well as losses in the transformer, on power lines, generators and other components. Most wind and solar power plants do not provide inertial response or control of statism [3]. A number of difficulties arise related to the stability of the voltage in transient modes.. In this regard, the actual issue is the introduction of adaptive controllers for controlling inverters, depending on the change in the mode parameters [4, 5]. In this paper, we present the results of studies on the modeling of transient regimes using the example of the SPP with an installed capacity of 2 MW describes the possibility of changing the principles of system management, which is the most economical solution to the problems of integrating wind and photovoltaic solar energy into a network. The virtual model of the PSCad analyzed the stability of the voltage in the event of a short circuit on the 10 kV bus, algorithms and mechanisms for using the intelligent controller for controlling the photovoltaic system were developed